Modulation of Murine Macrophage TLR7/8-Mediated Cytokine Expression by Mesenchymal Stem Cell-Conditioned Medium - Takahiro Asami; Makoto Ishii; Hideki Fujii; Ho Namkoong; Sadatomo Tasaka; Kenichi Matsushita; Ken Ishii; Kazuma Yagi; Hiroshi Fujiwara; Yohei Funatsu; Naoki Hasegawa; Tomoko Betsuyaku (Mediators of Inflammation)
Increasing evidence suggests that mesenchymal stem cells (MSCs) play anti-inflammatory roles during innate immune responses. However, little is known about the effect of MSCs or their secretions on the ligand response of Toll-like receptor (TLR) 7 and TLR8, receptors that recognize viral single-stranded RNA (ssRNA). Macrophages play a critical role in the innate immune response to ssRNA virus infection; therefore, we investigated the effect of MSC-conditioned medium on cytokine expression in macrophages following stimulation with TLR7/8 ligands. After stimulation with TLR7/8 ligand, bone marrow-derived macrophages cultured with MSCs or in MSC-conditioned medium expressed lower levels of tumor necrosis factor (TNF) α and interleukin (IL) 6 and higher levels of IL-10 compared to macrophages cultured without MSCs or in control medium, respectively. The modulations of cytokine expression were associated with prostaglandin E2 (PGE2) secreted by the MSCs. PGE2 enhanced extracellular signal-related kinase (ERK) signaling and suppressed nuclear factor-κB (NF-κB) signaling. Enhanced ERK signaling contributed to enhanced IL-10 production, and suppression of NF-κB signaling contributed to the low production of TNF-α. Collectively, these results indicate that MSCs and MSC-conditioned medium modulate the cytokine expression profile in macrophages following TLR7/8-mediated stimulation, which suggests that MSCs play an immunomodulatory role during ssRNA virus infection.